If you seek, you will find: second record of Melanoloma viatrix Hendel, 1911 (Diptera, Richardiidae) in pineapple in Brazil and its distribution in the country - Aprigio L. Oliveira-Filho; Israel S. Pinto; Hilda B. Luz; Thiago H. R. Pádua; Francisco Limeira-de-Oliveira; Ricardo Adaime; Marcoandre Savaris; Roberto A. Zucchi (Entomological Communications)
The pineapple fly, Melanoloma viatrix Hendel, 1911 (Diptera, Richardiidae), is a pest in pineapple plantations in several South American countries. In Brazil, pineapple damage by M. viatrix was first reported in a commercial plantation in the state of Amapá. We report this pest from a single pineapple sample collected in the municipality of Itaituba, state of Pará, from a plantation operated under the family farming system. As in other South American countries, pineapple is the sole known host of M. viatrix. Examination of specimens deposited in two Brazilian collections revealed that, in addition to the states of Amapá and Pará, M. viatrix also occurs in the states of Maranhão, Tocantins, and Mato Grosso. However, no host information is known for the specimens deposited in collections; therefore, M. viatrix is known to damage pineapple only in Amapá and Pará. Given the extensive geographical distribution of the pest, surveys of host plants and sampling in other Brazilian pineapple-producing states are needed to establish effective management strategies and prevent the spread of the pest within Brazil.